Optimalisasi UMKM di Kepulauan Mentawai Melalui Marketplace dan Digitalisasi Logistik - Dwi Welly Sukma Nirad; Rika Ampuh Hadiguna; Ahmad Syafruddin Indrapriyatna; Wahyudi; Ricky Akbar; Hafizah Hanim; Andrew Kurniawan Vadreas (Indonesian Society of Applied Science, 2023)
Economic growth in West Sumatra's Mentawai Islands is relatively undeveloped due to geographical conditions and human resource capacity. The status as a 3T region (Disadvantaged, Frontier, Outermost) inhibits Micro, Small, and Medium Enterprises (MSMEs) growth. Despite MSMEs being economic pillars that stimulate regional development, their progress remains slow. To counter this, our study proposes